Physical capacity and the motor tests relative for the health promotion in children and adolescents - Roberto Jerônimo dos Santos Silva (Universidade Federal de Santa Catarina, 2003)
This article discusses physical capacity and health-promotion-oriented motor tests in children and adolescents, in order to provide a foundation for future studies that intend to debate this topic. The idea of evaluating physical activity levels in a population is aimed to determine the level of physical fi tness, and to verify that this is in line with criteria for good health. From a functional point of view, .good health is defined by the following components: body composition (not considered in this article), strength, muscular endurance capacity and fl exibility. These components are measured by test batteries that are intended to measure the health of individuals and/or populations. The starting point for this debate is the published reference literature that classifi es motor tests as either norm-referenced or criterion-referenced standards. RESUMO Este artigo discute as capacidades físicas e os testes motores voltados à promoção da saúde em crianças e adolescentes, de forma a subsidiar trabalhos em que este tema esteja em voga. A idéia de avaliar a atividade física em uma população é baseada no desejo de determinar o estado de atividade atual da mesma, e verifi car se ela está de acordo com os critérios apropriados para uma boa saúde. Do ponto de vista morfofuncional, uma boa "saúde relatada" é defi nida a partir dos componentes: composição corporal (não abordado neste trabalho), força e resistência muscular e fl exibilidade, componentes estes que são verifi cados a partir da aplicação de testes ou baterias de testes que pretendem medir e verifi car os níveis individuais e/ou populacionais de saúde relatada. A literatura de referência, que classifi ca os testes motores como referenciados a partir de normas ou critérios é o ponto de partida para esse debate.